مساهمة في تحديث وتكثيف الشبكات الجيوديزية الموجودة في سورية باستخدام نظام التموضع العالمي GPS - فايز ديب (Tishreen University, 2019)
تُعَدُّ الشبكات الجيوديزية الأساس لجميع الأعمال المساحية الدقيقة، فتمَّ في هذا البحث مناقشة بعض المسائل والتوصيات المتعلقة بإمكانية استخدام نظام تحديد المواقع العالمي في تأسيس وتكثيف الشبكات الجيوديزية السورية. تم اختبار شبكتين جوديزيتين الأولى معرفة في جملة لامبير والثانية في الجملة الستيريوغرافية، وتم استخدام الطريقة الساكنة في نظام GPS لرصد الشبكة مع اعتبار أربع نقاط مرجعية. وتم تحويل إحداثيات الشبكة الفضائية المعدلة في WGS84 إلى نظام الإحداثيات المحلية (لامبير والستيريوغرافي). وتم حساب معاملات التحويل بين نظام المقارنة WGS84 ونظام المقارنة المستخدم محلياً Clarke 1880 لمنطقة الشبكة باستخدام النقاط المرجعية. كما تم حساب الفروقات بين الإحداثيات الجديدة والقديمة لنقاط الشبكة باستخدام معاملات التحويل السبعة. هذه الفروقات من مرتبة السنتيمترات لمسافات تصل إلى 10 كم تظهر دقة نظام الـGPS في تحديث الشبكات الجيوديزية وتكثيفها. Geodetic networks are considered an essential basis for all precise surveying works. Using GPS technology, this paper discusses some problems and recommendations that concern establishing and densifying Syrian geodetic networks. Two geodetic networks are tested: the first is defined in the Syrian Lambert projection and the second is defined within stereographic coordinates. We have used the static mode of GPS for observing networks taking into account four reference points. The GPS network adjusted in WGS84 is transformed to the local coordinates system (Syrian Lambert and stereographic). Using reference points, transformation parameters between WGS84 datum and Clarke 1880 datum are derived from the regional network. The differences between old and new coordinates are calculated using transformational parameters. These differences ranging from some centimeters to 10 km  in distance indicate the GPS accuracy in updating and densifying networks.